Capital Adjustment Patterns in Swedish Manufacturing Firms: What Model Do They Suggest? - Mikael Carlsson; Stefan Laséen (Sveriges Riksbank, 2002)
In this paper we study the capital adjustment process in Swedish manufacturing firms and relate the empirical findings to standard models of firm behavior in the presence of impediments to capital adjustments. We find that (i) an S,s model fits the data well in some, but not all, dimensions. (ii) A model with irreversible capital goes a long way in capturing the salient features of firm-level capital adjustment behavior. (iii) The partial adjustment model generally fails to explain capital adjustment patterns. (iv) The capital accumulation process is a highly volatile and non-persistent process on the firm-level. (v) Firms adjustment behavior is asymmetric in that they are more likely to tolerate excess capital than shortages of capital, and, finally, (vi) the estimated adjustment function implies that aggregate investment is relatively unresponsive to aggregate shocks in deep recessions as compared to normal times.
Keywords: D24; E22; L60; 330; Investment; Irreversibilities; Lumpiness; Manufacturing